ANALISIS CERITA RAKYAT EHIME OOKUGATA NI BAKETA FURUGITSUNE: STUDI KRITIS TERHADAP TEORI FUNGSI PELAKU CERITA RAKYAT VLADIMIR PROPP - Claudia Gretta Firstiasa (Universitas Diponegoro, 2013)
Abstract Folktales or folklores are always represent the culture of its civilization who created it. It means one folktale, even has similiraties with another folktales, will always brings uniqueness that can not be found in another folktales from another regions, and that uniqueness can not be generalized. In this research, the 31 functions of dramatis personae by Vladimir Propp which based on a research of 100 Russian’s folktales will be applied to a folktale from Ehime, Japan, Ookugata ni Baketa Furugitsune, in order to prove Propp’s statement that his functions of dramatis personae can be applied to all folktales around the world in general. The results show that Propp’s theory can be applied, but there are also deviations and addition. Those deviations and addition are influenced by Japan’s culture which is very different from Russian’s. It also shows the uniqueness of Japan’a culture. Keywords: folktale, function, culture, morphology, Propp.